The Relationship between The Level of Knowledge and Stigma Towards Leprosy Patients among Healthcare Workers - Prameswari, Laura Nanda; Rochyatul Jannah, Ayik; Wulandari Alshanti, Nadya (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Leprosy is currently one of the most common health problems in the world. Because leprosy is contagious and chronic, most people fear those who suffer from it, and leading to mindless creation of various negative stigmas. Purpose: This research aimed to determine the relationship between the level of knowledge and the stigma towards leprosy. Methods: This study used an analytical observational design with a cross-sectional approach, conducted from January to March 2024 at Pungging Health Community Center, Mojokerto Regency, East Java, Indonesia, using the total sampling method. We collected the data for this study using a questionnaire that included questions relevant to the variables under investigation. Processing and analyzing data used Microsoft Office Word 2019, Microsoft Office Excel 2019, and IBM SPSS Statistic 26. We used bivariate analysis the Spearman statistical test to determine the relationship between the dependent and independent variables. Result: Health workers with sufficient knowledge had the highest good stigma presentation (14%), and there is a significant relationship between the level of healthcare workers' knowledge of leprosy and stigma towards leprosy patients (p=0.025). Conclusion: A significant correlation exists between healthcare workers' understanding of the stigma associated with leprosy. To reach the program's target, health workers need additional training about leprosy to eliminate the negative stigma of healthcare workers towards leprosy.